The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1111/j.1469-8137.1996.tb04349.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological implications of recognition events in the pre‐infection stages of root pathogens

Abstract: SUMMARYHost-specificity and recognition by root-infecting pathogens are reviewed, with emphasis on fungi but drawing parallels with other root parasites, synnbionts and rhizosphere micro-organisms. Two major levels of specificity are identified; family-specific parasitism, exemplified by many parasites that characteristically infect Gramineae, and the possibly recent segregation of pathogen species into crop-specific strains. In both of these cases there are examples w^here host-specificity is paralleled by ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…In this context it would be interesting to search for factors responsible for the so-called docking known from other phytopathogenic oomycetes. These host factors seem to reorient the polarity of the zoospore during the attachment to the host cell such that the prospective germ-tube pole is aligned correctly (Deacon 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context it would be interesting to search for factors responsible for the so-called docking known from other phytopathogenic oomycetes. These host factors seem to reorient the polarity of the zoospore during the attachment to the host cell such that the prospective germ-tube pole is aligned correctly (Deacon 1996).…”
Section: Discussionmentioning
confidence: 99%
“…This so called adelphotaxis has been reported for the oomycete Achlya (Thomas and Peterson 1990). In most oomycetes, the polarity of the zoospores seems to be present, but during the attachment to the host cell (so-called docking) it is reoriented such that the prospective germ-tube pole is aligned correctly (Deacon 1996).…”
Section: Introductionmentioning
confidence: 97%
“…Numerous studies have demonstrated that preinfection processes of root‐infecting oomycetes are driven by host stimuli. This work has been described in several reviews (Carlile, 1987; Deacon, 1997; Tyler, 2002). In most cases, these stimuli appear to be general (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Very little is known of the factors influencing soil borne fungal pathogens in colonization of root tissues, although root-infecting fungi are important as diseasecausing agents (Deacon 1996). This lack of knowledge is in part a result of the difficulty of studying such processes below ground, and also because of the genetic intractability of many root-infecting organisms.…”
Section: Introductionmentioning
confidence: 99%